RELATIONSHIP OF KNOWLEDGE, ATTITUDE AND CULTURE WITH ANTENATAL CARE VISIT COMPLIANCE - Nurul Amalina; Ainal Mardiah; Eldawati Eldawati (Universitas Fort de Kock Bukittinggi, 2021)
Ante Natal Care (ANC) is the most important part of pregnancy. In the second quarterly PWS report, the highest maternal mortality came from Tebo district with 10 cases, of which ten cases of death were caused, among others, by 7 cases of bleeding and 3 cases of eclampsia/preeclampsia. This incident can be caused by the mother's non-compliance in the ANC examination. The purpose of the study was to determine the relationship between knowledge, attitude and culture with compliance with antenatal care visits in third trimester pregnant women in the working area of Suo-Suo Health Center, Tebo Regency in 2021. This study was a quantitative study with a cross sectional design. It was carried out in the working area of the Suo-Suo Health Center, Tebo Regency on August 16, 2021-August 31, 2021. The population was 43. The sample was 43 respondents using the total sampling technique. The statistical test used is the chi square test. The results showed that there was a significant relationship between knowledge (p= 0.004), attitude (p= 0.010) and culture (p= 0.011) with compliance with antenatal care visits in third trimester pregnant women in the working area of Suo-Suo Health Center, Tebo Regency in 2021. It is hoped that the Suo-suo Health Center can provide education to all pregnant women about the importance of carrying out complete ANC visits so that the health status of babies and mothers can be improved.